2016
DOI: 10.1017/pasa.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Chromospheric Activity Nature of KIC 9641031

Abstract: This study depends on KIC 9641031 eclipsing binary system with a chromospherically active component. There are three type variations, such as geometrical variations due to eclipses, sinusoidal variations due to the rotational modulations and also flares, in the light curves obtained with the data taken from the Kepler Mission Database. Taking into account results obtained from KIC 9641031's observations in the Kepler Mission Database, we present and discuss the details of chromospheric activity. The sinusoidal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…For instance, in the case of KOI-256, one of the interesting binary system observed by Kepler Satellite, the plateau value was found to be 2.3121±0.0964 s (Yoldaş & Dal 2017). In the case of FL Lyr, it was found to be 1.232±0.069 s (Yoldaş & Dal 2016). The flares compiled as Group 1 in this study behave as the same as flares detected from KOI-256, while Group 2 flares behave as the same as flares de-tected from FL Lyr.…”
Section: Discussion and Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…For instance, in the case of KOI-256, one of the interesting binary system observed by Kepler Satellite, the plateau value was found to be 2.3121±0.0964 s (Yoldaş & Dal 2017). In the case of FL Lyr, it was found to be 1.232±0.069 s (Yoldaş & Dal 2016). The flares compiled as Group 1 in this study behave as the same as flares detected from KOI-256, while Group 2 flares behave as the same as flares de-tected from FL Lyr.…”
Section: Discussion and Resultssupporting
confidence: 56%
“…The flares compiled as Group 1 in this study behave as the same as flares detected from KOI-256, while Group 2 flares behave as the same as flares de-tected from FL Lyr. Yoldaş & Dal (2016 revealed that both KOI-256 and FL Lyr have high level spot activity on their surfaces. Comparing these samples, one expects that both components of KIC 12418816 could exhibit spot activity depending on their plateau values.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…This value is 433.10 s for DO Cep ( B − V = 1 m .604), 334.30 s for EQ Peg, and 226.30 s for V1005 Ori (Dal & Evren 2011). In the same way, the half-life parameter is 2291.7 s for KIC 9641031, while it is 1014 s for KIC 9761199, which are binary systems including a dMe-type component (Yoldaş & Dal 2016, 2017). As a result, when the flare total time for the stars such as EQ Peg, V1005 Ori, and DO Cep reaches a few minutes, the their flare energies can easily reach the Plateau level.…”
Section: Resultsmentioning
confidence: 91%
“…The flare frequencies of KOI-256 were compared with the flare frequencies found from the young main-sequence dMe dwarfs, known as UV Ceti-type, exhibiting flare activity. The flare frequencies of KIC 9761199 were found to be N 1 = 0.01351 h −1 and N 2 = 0.00006 (Yoldaş & Dal 2016), while they were found to be N 1 = 0.01735 h −1 and N 2 = 0.00001 for KIC 9641031 (Yoldaş & Dal 2017). KOI-256, when compared to these two systems, seems to have the highest flare frequency values among similar systems.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation